Contribution of upregulated aminoacyl‐tRNA biosynthesis to metabolic dysregulation in gastric cancer. Issue 11 (1st August 2021) - Gao, Xiaoling; Guo, Rui; Li, Yonghong; Kang, Guolan; Wu, Yu; Cheng, Jia; Jia, Jing; Wang, Wanxia; Li, Zhenhao; Wang, Anqi; Xu, Hui; Jia, Yanjuan; et al.
Abstract: Background and Aim: Metabolic reprogramming is characterized by dysregulated levels of metabolites and metabolic enzymes. Integrated metabolomic and transcriptomic data analysis can help to elucidate changes in the levels of metabolites and metabolic enzymes, screen the core metabolic pathways, and develop novel therapeutic strategies for cancer. Methods: Here, the metabolome of gastric cancer tissues was determined using liquid chromatography–mass spectrometry. The transcriptome data from The Cancer Genome Atlas dataset were integrated with the liquid chromatography–mass spectrometry data to identify the common dysregulated gastric cancer‐specific metabolic pathways. Additionally, the protein expression and clinical significance of key metabolic enzymes were examined using a gastric cancer tissue array. Results: Metabolomic analysis of 16 gastric cancer tissues revealed that among the 15 dysregulated metabolomic pathways, the aminoacyl‐tRNA biosynthesis pathway in the gastric tissues was markedly upregulated relative to that in the adjacent noncancerous tissues, which was consistent with the results of transcriptome analysis. Bioinformatic analysis revealed that among the key regulators in the aminoacyl‐tRNA biosynthesis pathway, the expression levels of threonyl‐tRNA synthetase (TARS) and phenylalanyl‐tRNA synthetase (FARSB) were correlated with tumor grade and poor survival, respectively. Additionally, gastric tissue array data analysis indicated that TARS and FARSB were upregulated in gastric cancer tissues and were correlated with poor prognosis and tumor metastasis. Conclusions: This study demonstrated that the aminoacyl‐tRNA biosynthesis pathway is upregulated in gastric cancer and both TARS and FARSB play key roles in the progression of gastric cancer. Additionally, a novel therapeutic strategy for gastric cancer was proposed that involves targeting the aminoacyl‐tRNA biosynthesis pathway.